Renewable Energy Systems: Development and Perspectives of a Hybrid Solar-Wind System - Subrahmanyam, J. B. V.; Alluvada, P.; Bandana, .; Bhanupriya, K.; Shashidhar, C. (Engineering, Technology & Applied Science Research, 2012)
Considering the intermittent natural energy resources and the seasonal un-balance, a phtovoltaic-wind hybrid electrical power supply system was developed to accommodate remote locations where a conventional grid connection is inconvenient or expensive. However, the hybrid system can also be applied with grid connection and owners are allowed to sell excessive power back to the electric utility. The proposed set-up consists of a photo-voltaic solar-cell array, a mast mounted wind generator, lead-acid storage batteries, an inverter unit to convert DC to AC, electrical lighting loads, electrical heating loads, several fuse and junction boxes and associated wiring, and test instruments for measuring voltages, currents, power factors, and harmonic contamination data throughout the system. The proposed hybrid solar-wind power generating system can be extensively used to illustrate electrical concepts in hands-on laboratories and also for demonstrations in the Industrial Technology curriculum. This paper describes an analysis of local PV-wind hybrid systems for supplying electricity to a private house, farmhouse or small company with electrical power depending on the site needs. The major system components, work principle and specific working condition are presented.